2005
DOI: 10.1016/j.febslet.2005.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the subsite‐structure of vimelysin and thermolysin using FRETS‐libraries

Abstract: Vimelysin is a metalloproteinase with high activity at low temperature and an unusual resistance to organic solvents. Substrate specificities of vimelysin and thermolysin were examined using FRETS-libraries, revealing a significant difference at the P3 0 position: vimelysin preferred acidic amino acid residues, whereas thermolysin preferred basic residues. Homology modeling of vimelysin suggests that oppositely charged residues in the S3 0 subsites (R215 in vimelysin and D213 in thermolysin) may be responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Among M4 and M13 gluzincins, the S1′ specificity residues form a pocket that is the chief determinant of substrate specificity . In thermolysin (M4) and neprilysin (M13) X‐ray crystal structures, S1′ specificity pockets are composed of aromatic and hydrophobic residues favoring substrate P1′ side chains that possess complimentary hydrophobic character.…”
Section: Discussionsupporting
confidence: 58%
“…Among M4 and M13 gluzincins, the S1′ specificity residues form a pocket that is the chief determinant of substrate specificity . In thermolysin (M4) and neprilysin (M13) X‐ray crystal structures, S1′ specificity pockets are composed of aromatic and hydrophobic residues favoring substrate P1′ side chains that possess complimentary hydrophobic character.…”
Section: Discussionsupporting
confidence: 58%
“…Substrate specificity of the proteinase A novel type of fluorescence energy transfer (FRET) combinatorial library, which has been proven to be a sensitive and reliable substrate for determination of the substrate specificity of proteinases, 14,22,23) was used in order to determine the substrate specificity of the purified proteinase from Halobacillus sp. SR5-3.…”
Section: Amino-terminal Sequence Analysismentioning
confidence: 99%
“…Studies of cathepsin K showed that its unique collagenolytic activity among cathepsins is caused by a preference for arginine and lysine at the P1 position and proline and glycine at the P2 and P3 positions [28]; neither of these residues, especially proline, is preferred by other human cathepsins. Previously, we have studied the residue preferences in SOT and SGT using fluorescence energy transfer substrate (FRETS) combinatorial libraries [29–31], which consist of a total of 475 peptide substrates. In contrast with other studies, we found that the P1, P2 and P3 preferences of SOT resembled those of SGT.…”
Section: Resultsmentioning
confidence: 99%